Semi-refined carrageenan/glycerol/α-tocopherol hybrid films as active packaging for extending the shelf life of meat - Khadijah Husna, Abd Hamid (2019)
This study focuses on the development and characterization of semi-refined carrageenan film incorporated with α-tocopherol for active packaging application. Semi-refined carrageenan film plasticized with glycerol and incorporated with α-tocopherol was prepared using casting method. The concentration of plasticizer glycerol was determined to improve the mechanical and physical properties of semi-refined carrageenan films. The properties of semi-refined carrageenan/glycerol/α-tocopherol hybrid films as active packaging were characterized. Thereafter, the effectiveness of semi-refined carrageenan/glycerol/α-tocopherol hybrid films as active packaging film to extend the shelf life of meat patties were evaluated. This study revealed that semi-refined carrageenan film plasticized with glycerol could improve the mechanical properties of developed film compared to that of the control film (semi-refined carrageenan without the addition of plasticizer). This can be shown at the value of elongation at break which is significantly increased (p < 0.05) with the increase of glycerol concentration and the values were range from 7.33% to 16.33%. Further, semi-refined carrageenan film with higher concentration of glycerol (0.9% and 1.2% [v/v]) showed an improvement on the transparency properties as the opacity value decreased with the increase of glycerol concentration. Another hand, the film solubility and moisture content were increased as the concentration of glycerol on the film development was increased. The result displayed that the higher film solubility and moisture content may be due to the hydrophilicity properties of semi-refined carrageenan and glycerol used on the film development. Nonetheless, the incorporation of α-tocopherol at any concentrations (0.1%, 0.2%, 0.3% 0.4% [v/v]) improved the mechanical properties of semi-refined carrageenan-based film. This can be shown at the higher value of elongation at break (13.67% to 20.00%) as compared to that of the control film (0.83%). The opacity value of semi-refined carrageenan film incorporated with α-tocopherol (6.88 to 8.13 mm–1) was lower than that of the control film (9.03 mm–1). Besides that, the film solubility and moisture content values were decreased with the incorporation of α-tocopherol. In spite of this, the release of antioxidant from the films were observed using DPPH scavenging activity and higher total phenolic content on 95% (of ethanol) food simulant during 30-days storage. Semi-refined carrageenan film with α-tocopherol exhibited higher antioxidant activity which could achieve 90% during storage compared to that of the control film. Moreover, meat patties wrapped with antioxidant film revealed lower development of lipid oxidation under refrigerated storage for 12-days. Furthermore, the brown color development was much slower with the meat that wrapped with antioxidant film compared to that of the meat wrapped with the control film under refrigerated condition. Thus, the development of semi-refined carrageenan film incorporated with α-tocopherol as active packaging could be an alternative packaging that might enhance the shelf life of meat under refrigerated condition.